Causes of the growth crisis in the EC countries and strategies for overcoming it - Thomas Baum (Intereconomics, 1984)
Whereas in 1970 most of the large EC countries were still recording real growth rates in excess of 5%, after the two oil crises there was an appreciable slowdown in economic expansion and at the beginning of the eighties even a real contraction. At the same time unemployment increased dramatically. Where do the causes of the crisis lie? What strategies promise success in overcoming it?
Keywords: 330; EC